Outcomes of Mycobacterium avium complex lung disease based on clinical phenotype. Issue 3 (28th September 2017) - Koh, Won-Jung; Moon, Seong Mi; Kim, Su-Young; Woo, Min-Ah; Kim, Seonwoo; Jhun, Byung Woo; Park, Hye Yun; Jeon, Kyeongman; Huh, Hee Jae; Ki, Chang-Seok; Lee, Nam Yong; Chung, Myung Jin; et al.
The effect of the clinical phenotype of Mycobacterium avium complex (MAC) lung disease on treatment outcome and redevelopment of nontuberculous mycobacterial (NTM) lung disease after treatment completion has not been studied systematically. We evaluated 481 treatment-naïve patients with MAC lung disease who underwent antibiotic treatment for ≥12 months between January 2002 and December 2013. Out of 481 patients, 278 (58%) had noncavitary nodular bronchiectatic (NB) disease, 80 (17%) had cavitary NB disease and 123 (25%) had fibrocavitary disease. Favourable outcome was higher in patients with noncavitary disease (88%) than in patients with cavitary disease (76% for fibrocavitary and 78% for cavitary NB disease; p<0.05). Cavitary disease was independently associated with unfavourable outcomes (p<0.05). Out of 402 patients with favourable outcomes, 118 (29%) experienced redevelopment of NTM lung disease, with the same MAC species recurring in 65 (55%) patients. The NB form was an independent risk factor for redevelopment of NTM lung disease (p<0.05). In patients with recurrent MAC lung disease due to the same species, bacterial genotyping revealed that 74% of cases were attributable to reinfection and 26% to relapse. Treatment outcomes and redevelopment of NTM lung disease after treatment completion differed by clinical phenotype of MAC lung disease. Treatment outcomes differ according to clinical phenotype in patients with Mycobacterium avium complex lung disease http://ow.ly/g4WU30dbLHQ